Increase in Land Value due to Spatial Transformation in the Northern Part of the Bandung â Cimahi Peri-urban Region - Anita Vitriana (Journal of Regional and City Planning, 2017)
Abstract. The increase in density and urban activity has led to spatial expansion towards the urban periphery. Peri-urban areas that originally were rural areas, gradually turn into typical urban settlement areas. This transformation is followed by an increase in economic land value which is characterized by an increase in land price.  This study examines the meaning of the increase in economic land value for the government as an effect of the spatial transformation in the periphery area of Bandung City and the northern part of Cimahi. This study uses quantitative-qualitative mixed methods. Primary data was obtained through interviews with informants from local communities, and secondary data was obtained from a former study on this area and Land and Building Tax documentation (PBB). For the government, economic land value specifically will be reviewed using the Land-Tax Object Sales Value (NJOP Tanah), and then compared with the increase in market price of land. The study results show that the increase of land price due to the spatial transformation in the Gunung Batu Dalam area was not in line with the increase in land value for local governments. The increase in land prices determined by market forces becomes a potential loss of revenue for local governments. Therefore, the government needs to control the increase in land prices. If not, then the government should immediately adjust the Land-Tax Object Sales Value to represent the economic land value of peri-urban areas.Keywords. land value, spatial transformation, peri-urban area, Gunung Batu Dalam area.Abstrak. Peningkatan kepadatan dan aktivitas urban telah menyebabkan terjadinya perubahan spasial ke arah periferi kota.  Wilayah peri-urban yang sebelumnya daerah perdesaan, lambat laun berubah menjadi wilayah permukiman khas perkotaan. Perubahan fungsi tersebut berdampak pada peningkatan nilai ekonomi lahan. Studi ini mengkaji makna peningkatan nilai ekonomi lahan bagi pemerintah sebagai dampak proses transformasi lahan pada salah satu kawasan periferi Kota Bandung-Cimahi bagian utara. Penelitian ini menggunakan pendekatan kuantitatif-kualitatif. Data primer diperoleh melalui metoda wawancara dengan informan dari komunitas lokal, dan data sekunder diperoleh dari penelitian yang pernah dilakukan sebelumnya terhadap kawasan ini serta dokumentasi Pajak Bumi dan Bangunan (PBB). Hasil penelitian menunjukkan bahwa peningkatan harga lahan akibat transformasi spasial di Kawasan Gunung Batu Dalam tidak berbanding lurus dengan peningkatan nilai lahan bagi pemerintah daerah. Peningkatan harga lahan yang ditentukan oleh mekanisme pasar, justru menjadi celah potensi kehilangan pendapatan bagi pemerintah daerah. Untuk itu, pemerintah perlu mengontrol peningkatan harga tanah. Jika tidak, maka pemerintah perlu segera menyesuaikan Nilai Jual Objek Pajak (NJOP) Tanah agar secara reprsentatif dapat mewakili nilai ekonomi lahan kawasan peri-urban.  Kata kunci. Nilai lahan, transformasi spasial, wilayah peri-urban, Kawasan Gunung Batu Dalam